1994
DOI: 10.1152/jn.1994.72.2.1037
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically silent sodium channels in mammalian outer hair cells

Abstract: 1. Voltage-dependent properties of isolated guinea pig outer hair cells (OHCs) were investigated using whole-cell recording. An inward current was detected in approximately 10% of the cells. This inward current was identified as belonging to the voltage-activated sodium current family on the basis of its high sensitivity to tetrodotoxin and the effect of substitution of impermeant ions. Although this is the first report of a sodium current in the mammalian cochlea, it differs from the classical neuronal sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…This current is not present in adult guinea-pig inner hair cells but has been observed in possibly younger adult guinea-pig outer hair cells in one study [34]. Similar currents have been seen in hair cells from the embryonic chick otocyst [32] and neonatal mouse utricle [30].…”
Section: Properties Of I H In Ub/oc-2 Cell Linesupporting
confidence: 63%
“…This current is not present in adult guinea-pig inner hair cells but has been observed in possibly younger adult guinea-pig outer hair cells in one study [34]. Similar currents have been seen in hair cells from the embryonic chick otocyst [32] and neonatal mouse utricle [30].…”
Section: Properties Of I H In Ub/oc-2 Cell Linesupporting
confidence: 63%
“…G Na in embryonic vestibular hair cells is almost completely inactivated at typical resting potentials, suggesting that it is physiologically silent, similar to the sodium conductance in outer hair cells (Witt et al, 1994). However, we cannot exclude the possibility that the in vivo properties differ from those we described in vitro.…”
Section: Receptor Potentialsmentioning
confidence: 66%
“…Transient expression of sodium currents has been documented in auditory hair cells (Evans and Fuchs, 1987;Witt et al, 1994;Oliver et al, 1997;Marcotti et al, 2003) but has not been widely reported in vestibular cells (Masetto et al, 2003). One preliminary report suggested the presence of TTX-resistant sodium currents in mammalian vestibular hair cells (Rüsch and Eatock, 1997).…”
Section: Sodium Conductancementioning
confidence: 99%
“…We found a rapidly activating, rapidly inactivating inward Na ϩ current in postnatal SCC rat and gerbil hair cells. A transient sodium current, I Na , has been described previously in hair cells from mouse and rat utricle (2,14,19,35), mouse, rat and guinea pig cochlea (20,24,34) and chicken vestibular system (23,33). In mouse utricle I Na peaked at E16 -E18 and subsequently declined to almost zero at birth (14).…”
Section: Discussionmentioning
confidence: 82%